Endometrial expression of e-cadherin in relation to estrogen-progesterone receptor characteristics of the endometrium - S. S. Aganezov; V. N. Ellinidi; A. V. Morotskaya; A. S. Artemyeva; A. O. Nyuganen; N. V. Aganezova (Акушерство, гинекология и репродукция)
Aim: to evaluate the endometrial expression of e-cadherin in relation to the estrogen-progesterone-receptor status of the endometrium.Materials and methods. In total 137 women were examined including 81 patients with infertility and 40 with a history of early pregnancy loss (main group); for comparison, 16 healthy fertile women (control group) were also examined. Endometrial aspiration biopsy was performed on 6–8 days after ovulation; in parallel, a peripheral blood sample was taken to determine the levels of estradiol and progesterone. A histological and immunohistochemical study of the endometrium with determination of estrogen (ER) and progesterone (PR) receptors and e-cadherin expression was carried out.Results. All fertile women (n = 16) and only 44 % (n = 53) of patients in the main group had the normal pattern of hormonereceptor endometrial interactions, i. e., low expression of ER and PR in the endometrial glands as well as reduced expression of ER and high expression of PR in the endometrial stroma. The endometrial e-cadherin expression was assessed in the following cohorts: a) women with normal hormone-receptor interactions (16 women in the control group and 53 women in the main group); b) with abnormal variants of hormone-receptor interactions in the endometrium (68 patients in the main group). The frequency of reduced e-cadherin expression was significantly lower in the cohort of women with normal estrogenprogesterone-receptor endometrial status (a) than in the cohort of women with abnormal variants of the endometrial “response” (b): in the luminal epithelium – in 5 % (3 out of 63) (а) vs. 17 % (8 out of 47) (b) (p < 0.05); in the glands – in 13 % (9 out of 69) (a) vs. 37 % (25 out of 68) (b) (p < 0.05).Conclusion. The estrogen-progesterone-receptor status of the endometrium is significant for the e-cadherin expression in the luminal epithelium and glands of the endometrium.